2019
DOI: 10.1002/jcp.28706
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells modified by angiogenin‐1 promotes tissue repair in mice with oxygen‐induced retinopathy of prematurity by promoting retinal stem cell proliferation and differentiation

Abstract: Retinopathy has become one of the major factors that lead to blindness worldwide.Although many clinical therapies are concerned about such disease, most of them focus on symptoms alleviation. In this study, we aim to investigate whether coculture retinal stem cells (RSCs) with bone marrow mesenchymal stem cells transfected with angiogenin-1 (Ang-1-BMSCs) affects the damaged retinal tissue of oxygen-induced retinopathy of prematurity (OIR-ROP) mice. After OIR-ROP mouse model establishment, Ang-1-BMSCs, RSCs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Interestingly, many of the identified proteins are related to both development and degeneration, representing impaired function at both ends of the lifespan. This is illustrated by the association of APP to both neurogenesis and neurodegenerative diseases as well as the correlation of ANGPT1 with both ROP and diabetic retinopathy 58 , 64 , 114 , 116 , 124 126 . Further on, there is a clear association between osteogenesis and bone metabolism, a mechanism one can believe is connected to hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, many of the identified proteins are related to both development and degeneration, representing impaired function at both ends of the lifespan. This is illustrated by the association of APP to both neurogenesis and neurodegenerative diseases as well as the correlation of ANGPT1 with both ROP and diabetic retinopathy 58 , 64 , 114 , 116 , 124 126 . Further on, there is a clear association between osteogenesis and bone metabolism, a mechanism one can believe is connected to hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some of the proteins have been acknowledged for the possible involvement in diabetic retinopathy or ROP: AGER, ANGPT1, CD40LG, GDF2, MMP12, SERPINE1, THBD, DKK1, PDGFA, and IL-18. 47 , 50 , 51 , 54 , 56 , 58 , 92 , 101 , 114 123 For example, Lamine et al 115 presented recently that CD40LG is associated to both occurrence and severity of type 2 diabetic retinopathy, which shares some physiological connections with ROP. Interestingly, many of the identified proteins are related to both development and degeneration, representing impaired function at both ends of the lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal SCs (RSCs) can migrate, differentiate, and integrate into the retina ( Figure 16 ) [ 164 ]. The co-culture of BM-MSCs and RSCs transfected with Angular-1 can induce the differentiation of RSCs into β-tubulin and PKC, promote the expression of Ang-1 and IGF-1 and proliferation and differentiation of RSCs, and effectively improve the therapeutic effect of OIR-ROP in rats with retinal injury [ 165 ]. Other studies have suggested that BM-MSCs transfected with Ang-1 could improve the morphology of the injured optic nerve and repair the myelin sheath of nerve fibers, demonstrating its preventive and therapeutic effects on optic nerve injury in OIR rats [ 166 ].…”
Section: Application Of Scs In Refractory Diseases Of Newbornsmentioning
confidence: 99%
“…Injected eyes displayed a significantly reduced avascular area and prevention of neovascularization. Other than eEPC and OEC, the effect of mesenchymal stem cells (MSCs) and adipose-derived stem cells (ASCs) were reported recently using the mouse OIR model [232,233,234,235]. MSCs or ASCs were injected into the OIR-treated mice at P12 intravitreally.…”
Section: Stem Cell Therapy In Ropmentioning
confidence: 99%